Media richness as a strategy to enhance local tourism: Effects on tourist satisfaction and revisit intention - Arisman, Ari; Hendrayati, Heny; Rahmat, Adhitya; Marimon, Frederic (Asian Management and Business Review, 2026)
Tourist revisit intention is a key element of the success of the tourism industry. This study analyzes the relationship between media richness and revisit intention, with perceived enjoyment, perceived usefulness, perceived aesthetics, and satisfaction. A survey was conducted on 240 tourists at a local tourism destination themed “tourist village” using a bipolar adjective scale. Data were analyzed using structural equation modeling (SEM) with partial least square using SmartPLS 3.0. The findings indicate that media richness influenced perceived enjoyment, perceived usefulness, and perceived aesthetics. Perceived enjoyment and perceived aesthetics then influenced satisfaction. Meanwhile, perceived usefulness did not influence satisfaction. Tourist satisfaction ultimately influenced revisit intention. These findings highlight the importance of media richness in 2D visual media that can create positive tourist perceptions, increase satisfaction, and encourage repeat visits to local destinations. This study provides practical insights for tourism managers to utilize digital media by focusing on media richness, perceived enjoyment, perceived usefulness, perceived aesthetics, and satisfaction to improve destination competitiveness.